CONTRASTIVE PERSPECTIVES ON THE RELIABILITY OF GRAMMAR TESTING: THE CASE OF THE VERB PHRASE IN L2 ENGLISH - Jacobs, Geert; Braecke, Chis (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract In this article we present the preliminary results of empirical research on the reliability of grammar testing. The following testing techniques are examined: multiple choice, translation, gap-filling and, finally, performance. In particular, for the purposes of this paper we set up four different tests to identify knowledge of the English verb phrase among native speakers of Dutch. Drawing from a detailed examination of selected results it is concluded that a renewed interest in a contrastive approach to language testing and practice is to be recommended.